Анализ электродинамических усилий в индукционной индукторной системе с массивным неферромагнитным экраном и ферромагнитной листовой заготовкой - Батыгин, Ю.В.; Гнатов, А.В.; Щиголева, С.А.; Барбашова, М.В. (Електротехніка і електромеханіка, 2011)
The article is devoted to functioning of an induction inductor system with a nonferromagnetic massive screen and a ferromagnetic thin-walled sheet workpiece in a low-frequency mode of operating fields. Radial distribution of induced currents density, Lorenz force, Ampere force and the force specified by the workpiece magnetic properties in the system considered is analyzed. Magnetic properties of the workpiece metal are shown not to substantially influence electrodynamic processes characteristics.